Trends in self-reported dilated eye examinations among diabetic adults in California from 2011 to 2021 - Xiaoli Niu; Bruce Burkemper; Xuejuan Jiang (PLoS ONE, 2025)
Although prior studies have documented disparities in eye care utilization by age, race/ethnicity, sex, and socioeconomic status, limited research has tracked long-term trends within the diabetic population in California, particularly in the context of the COVID-19 pandemic. We aimed to estimate the 11-year secular trend in eye care utilization among adult diabetic patients in California, USA. This was a secondary analysis of public-use data from the California Health Interview Survey (CHIS), an annual population-based survey in California conducted from 2011 to 2021. CHIS samples a representative portion of the California population, with over 20,000 adults in each survey cycle. Data analyses were conducted from January 2023 to April 2024. The primary outcome was the weighted percentage of diabetic adults who reported undergoing a dilated eye exam within the past year. Survey-weighted multivariable logistic regression analyses were conducted to evaluate the association between sociodemographic risk factors and the outcome. The prevalence of recent dilated eye exams declined by 8.3% (95% confidence interval -– CI: 4.7%−11.8%; P < 0.0001) in the two years following the onset of the COVID-19 pandemic (2020−2021) compared to the two years prior (2018−2019) among adults with diabetes in California. This decline was more pronounced among adults aged ≥ 60 years (P = 0.040 for age interaction) and was limited to urban residents (P = 0.030 for interaction with geographic area). However, it did not disproportionately affect Hispanic or Black Americans (P = 0.71 for race/ethnicity interaction). In conclusion, eye care utilization among the diabetic adults in California declined significantly from 2018−2019–2020−2021, a trend largely attributable to the impact of the COVID-19 pandemic.